PERANAN HUKUM NEGARA DALAM MENJAGA KEADILAN DAN KETERTIBAN MASYARAKAT - Aliza Qory Imeltha (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
State law plays a vital role in maintaining justice and order in society. This article discusses the function of state law in protecting citizens' rights, regulating community behavior, and upholding justice. This study uses a qualitative descriptive method by reviewing relevant literature and analyzing laws and regulations in force in Indonesia. The results of the study indicate that state law plays an important role in creating a just and orderly social order, as well as in maintaining national stability.